2021
DOI: 10.3390/app11041578
|View full text |Cite
|
Sign up to set email alerts
|

Cycle Logistics Projects in Europe: Intertwining Bike-Related Success Factors and Region-Specific Public Policies with Economic Results

Abstract: The aim of this paper is to investigate whether and which specific, distinctive characteristics of European cycle logistics projects and the corresponding supporting policies have an impact on their economic performances in terms of profit and profitability. First, we identify project success factors by geographic area and project-specific characteristics; then, we statistically test possible dependence relationships with supporting policies and economic results. Finally, we provide a value-based identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Based on the analysis of 50 city logistics projects, a study concluded that cargo bikebased city logistics solutions could lead to high profit. The authors of this paper highlighted that their result is coherent, and other studies proved the same advantages, not only from an economic point of view but also in terms of the environment and the quality of life [26].…”
Section: Existing City Logistics Systems With Cargo Bikessupporting
confidence: 61%
“…Based on the analysis of 50 city logistics projects, a study concluded that cargo bikebased city logistics solutions could lead to high profit. The authors of this paper highlighted that their result is coherent, and other studies proved the same advantages, not only from an economic point of view but also in terms of the environment and the quality of life [26].…”
Section: Existing City Logistics Systems With Cargo Bikessupporting
confidence: 61%
“…The main objective of this paper is to understand the differences between shared e-scooter users and non-users, and to identify the factors that influence their decisions to use or not use shared e-scooters. A lack of risk perception, awareness and regulation have been cited as key barriers to cycle logistic implementation across European cities [32]. In this regard, we investigate how shared e-scooter users and non-users perceive e-scooters differently on different topics concerning demographics, trip characteristics, safety, comparisons to shared e-bicycles, perceptions on risk taking and technology adoption profiles.…”
Section: Research Gapsmentioning
confidence: 99%
“…To decrease the CO 2 emissions, which are the main component of GHGs, the policy makers in the EU use almost 700 measures to address road transport emissions [11], and to decrease the demand for polluting cars and promote the use and production of more energy-efficient vehicles [16,29,30]. They use "push" or "pull" strategies, [31,32].…”
Section: Literature Review 21 Carbon Dioxide Emissions Of Passenger C...mentioning
confidence: 99%